Jane Addams and Hull-House - Goldish, Meish (Zaner-Bloser, Inc.)
This book is a biography of Jane Addams who spent her whole life getting important things done. She worked hard, as her father had taught her. She helped people in Chicago and across the country. In 1931, she became the first woman ever to win the Nobel Peace Prize...
Keywords: Juvenile Non-Fiction / Biographies